A pilot study for determination of anxiety related SLC6A4 promoter "S" and "L" alleles in healthy Turkish athletes - Corak, A.; Kapici, S.; Sercan, C.; Akkoç, O.; Ulucan, K. (Cellular and Molecular Biology, 2017)
We aimed to analyze the allelic distribution of solute carrier family-6 member-4 promoter region in Turkish athletes. Recent studies showed the association of lesser expressing "S" allele with anxiety. Genotype percentages for LL, LS and SS genotypes were found as 46, 35 and 19, respectively. 38% of the males had LL, %38 had LS and 24% had SS genotypes. Percentages of LL, LS and SS genotypes were 54, 31 and 15 in females, respectively. 15 (58%) male and 18 (69%) females had L, 11 (42%) male and 8 (31%) females had S alleles. Variations in the association of the SLC6A4 alleles with neuropsychiatric disorders according to different nationalities have been reported. This is the first report showing that LL genotype and L allele in Turkish athletes was more frequent than SS genotype and S allele.